Irish language film policy in Ireland - Crosson, Seán (Irish Journal of Arts Management and Cultural Policy, 2024)
Irish language cinema has experienced unprecedented growth and exposure in recent years, particularly with the critical and commercial success of An Cailín Ciúin [The Quiet Girl] (2022). Winner of The Grand Prix of the International Jury at the Berlin International Film Festival in February 2022, the film subsequently received a large number of further national and international awards including 8 Irish Film & Television Academy (IFTA) awards and culminating with its nomination on January 24 2023 for the Best International Feature Film Oscar, the first Irish-language production to receive such recognition. This article provides a historical context for understanding the achievement of An Cailín Ciúin in light of the development of policy with regard to Irish language cinema in Ireland. It will chart the emergence of the sector from the silent period through to recent developments, and identify key moments in the historical development of film production in the Irish language, including the establishment of TG4 (originally titled TnaG (Teilifís na Gaeilge)) in 1996, the enactment of the Broadcasting (Funding) Act 2003, and the launch of the Cine4 scheme in 2017.